Stability Analysis and Robust PID Control of Cable Driven Robots Considering Elasticity in Cables - M. A. Khosravi; Hamid D. Taghirad (AUT Journal of Electrical Engineering, 2016)
In this paper robust PID control of fully-constrained cable driven parallel manipulators with elastic cables is studied in detail. In dynamic analysis, it is assumed that the dominant dynamics of cable can be approximated by linear axial spring. To develop the idea of control for cable robots with elastic cables, a robust PID control for cable driven robots with ideal rigid cables is firstly designed and then, this controller is modified for the robots with elastic cables. To overcome vibrations caused by inevitable elasticity of cables, a composite control law is proposed based on singular perturbation theory. The proposed control algorithm includes robust PID control for corresponding rigid model and a corrective term. Using the proposed control algorithm the dynamics of the cable driven robot is divided into slow and fast subsystems. Then, based on the results of singular perturbation theory, stability analysis of the total system is performed. Finally, the effectiveness of the proposed control law is investigated through several simulations on a planar cable driven robot.